Quezon City Food Bank a battle against food loss and waste - Chang, Daryl Royce M. (College of Architecture, University of the Philippines Diliman, 2022)
Despite being an agricultural country, the Philippines continues to face problems with food security. At the same time, more than a thousand metric tons of food are lost and wasted every day. In line with achieving food security, this project identifies the causes of food and waste. Food loss refers to the loss of food in the production stages from harvest, to processing and storage, to distribution. Food waste, on the other hand, refers to the wasted food in the retail and consumption stages specifically in restaurants, markets and households. By studying successful food banks and food pantry systems in other countries, this project aims to establish a food sorting, storing, and distribution system in Quezon City and its barangays. Although the poverty rate in Quezon City is relatively low compared to the other cities in Metro Manila, the gap between the urban rich and poor is still evident. This project aims to bridge that gap by diverting both food loss and food waste to the citizens facing food insecurity and hunger.